SISTEM INFORMASI GEOGRAFIS (GIS) PENDISTRIBUSIAN DAGING QURBAN BERBASIS APLIKASI WEB - Indra Maulana Yusup Kusumah; Mida Tsamrotul Hamidah; Linda Apriyanti (LPPM STMIK Bandung, 2020)
Every year, during the sacrificial animal slaughter on Eid al-Adha, there is often an imbalance in the distribution of qurban meat between different regions. Additionally, the lack of coordination among qurban animal committees can result in either an excess or shortage of qurban meat in specific locations. Therefore, the implementation of a web-based Geographic Information System (GIS) for the distribution of qurban meat is an effort to manage this distribution effectively. The information system used in this study is a GIS-based application for qurban meat distribution, utilizing the Google Maps API. This application is designed to distribute qurban meat to the nearest locations. Furthermore, the application includes features such as displaying location information, visualizing maps integrated with Google Maps, and providing directions to locations. This web-based application is accessible only through a web browser and is developed using PHP and MySQL for database management. The goal of this system is to facilitate the even distribution of qurban meat.